2023
DOI: 10.1101/2023.03.12.532249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Volumetric analysis of the terminal ductal lobular unit architecture and cell phenotypes in the human breast

Abstract: The major lactiferous ducts of the human breast branch out and ultimately end at terminal ductal lobular units (TDLUs). These glandular structures are the source of milk upon lactation, and also the most common origin of breast cancer. Despite their functional and clinical importance, the three dimensional (3D) architecture of TDLUs has remained undetermined, largely due to their absence in rodent animal models. By utilizing recent technological advances in optical tissue clearing and microscopy, we imaged the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
(173 reference statements)
1
3
0
Order By: Relevance
“…Our findings revealed that as the bowl-shaped microwell radius increased from 25 to 100 μm, the Gaussian curvature at the microwell entrance decreased from ≈ −10 −2 to −10 −3 μm −1 (Figure 2d). Importantly, we demonstrated a strong correspondence between this range of Gaussian curvatures and the typical values of Gaussian curvature observed in anatomic lobular structures within the lung, [23] kidney, [24] breast, [25] and pancreas [12] (Figure 2e). Our findings underscore therefore the clinical relevance of bowl-shaped microwells to investigate the mechanoresponse of curved epithelial monolayers that line lobular structures.…”
Section: Gaussian Curvature Of Microwells Matches the Curvature Range...supporting
confidence: 64%
See 2 more Smart Citations
“…Our findings revealed that as the bowl-shaped microwell radius increased from 25 to 100 μm, the Gaussian curvature at the microwell entrance decreased from ≈ −10 −2 to −10 −3 μm −1 (Figure 2d). Importantly, we demonstrated a strong correspondence between this range of Gaussian curvatures and the typical values of Gaussian curvature observed in anatomic lobular structures within the lung, [23] kidney, [24] breast, [25] and pancreas [12] (Figure 2e). Our findings underscore therefore the clinical relevance of bowl-shaped microwells to investigate the mechanoresponse of curved epithelial monolayers that line lobular structures.…”
Section: Gaussian Curvature Of Microwells Matches the Curvature Range...supporting
confidence: 64%
“…To get further insight into this phenomenon, we used a MDCK cell line expressing red fluorescent E-cadherin at Each point corresponds to one replicate with n ≥ 5 microwells per replicate. E) Typical Gaussian curvatures in the lobular structures of four human organs: lung (in green), kidney [23,24] (in orange), breast [25] (in purple), and pancreas [12] (in blue).…”
Section: The Centripetal Orientation Of Cells Around the Microwell Ed...mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent influx of spatially-resolved studies is starting to give us unprecedented access to molecular and cellular patterns of spatial organization (Xia et al, 2019;Galeano Niño et al, 2022;Ratz et al, 2022;Rodriques et al, 2019;Zhao et al, 2022;Erickson et al, 2022;Lomakin et al, 2022;Peurla et al, 2023;Gomariz et al, 2018;Rindone et al, 2021;Rendeiro et al, 2021;Goltsev et al, 2018;Mondragón-Palomino et al, 2022). While classic models in population genetic theory have been extraordinarily important for producing initial testable predictions about the role of space and structure in evolution, most previous modeling approaches represent spatial structure as a small number of distinct patches, symmetrically connected by migration corridors (Wright, 1943;Kimura and Weiss, 1964;Carja et al, 2014;Maruyama, 1970a;Slatkin, 1981;Whitlock and Barton, 1997;Whitlock, 2003;Wakeley, 2000;Durrett and Levin, 1994;Whitlock et al, 1995;Petkova et al, 2016;Gutenkunst et al, 2009;Jackson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%